Anatomical, Physiological, and Technical Considerations of the Trapezius–rhomboid Plane Block - Leonardo Arce Gálvez; Jesús Daes Mora; David Hernández Abuchaibe; José Luis Cuervo Pulgarín; Christian Vladimir Guauque Marcelo; Rafael Enrico Valencia Gómez (Indian Journal of Pain)
Introduction: Myofascial pain syndrome (MPS) is a common cause of pain. The trapezius and rhomboid muscles in the dorsal region are a frequent location because of their anatomical location and mechanical loading. An interfacial block technique has been described that intervenes this syndrome in this specific location. Materials and Methods: A trapezius–rhomboid plane block (TRB) was performed in six patients diagnosed with dorsal MPS. The procedure was performed with ultrasonographic guidance, using 10 mL of 0.25% bupivacaine and 40 mg of methylprednisolone. An additional 2 mL of contrast was applied for fluoroscopic confirmation of the interfacial distribution. Results: A pain improvement of up to 80% was achieved in a follow-up performed up to week 10. No complications occurred, and we were able to illustrate the interfacial distribution in this plane, in addition to being able to theorize its mechanism of action in the blockade of the ventral cutaneous sensory branches, the terminal branches of the accessory nerve, and the dorsal nerve of the scapula. Conclusions: Our study develops an anatomical analysis of a recently described procedure and demonstrates a wide interfacial distribution with favorable clinical outcomes without complications, making it an interesting therapeutic tool in the management of dorsal MPS.